Corneal Confocal Microscopy Demonstrates Corneal Nerve Loss in Patients With Trigeminal Neuralgia - Lee, John-Ih; Böcking, Theresa; Holle-Lee, Dagny; Malik, Rayaz A.; Kieseier, Bernd C.; Hartung, Hans-Peter; Guthoff, Rainer; Kleinschnitz, Christoph; Stettner, Mark (Frontiers in Neurology, 2020)
Background The diagnosis of trigeminal neuralgia (TN) is challenging due to the lack of objective diagnostics. Corneal confocal microscopy (CCM) is a non-invasive ophthalmic imaging technique, which allows quantification of corneal nerve fibers arising from the trigeminal ganglion and may allow assessment of neurodegeneration in TN. Methods CCM was undertaken in 11 patients with TN and 11 age-matched healthy controls. Corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), corneal nerve fiber length (CNFL), corneal nerve fiber width (CNFW), corneal nerve fiber area (CNFA), dendritic cell (DC) and non- dendritic cell (NC) density with (F) or without (P) nerve fiber contact were quantified. Results Patients with TN had significantly lower CNFD and CNFL but no difference for any other corneal nerve or dendritic cell parameter in the ipsilateral and contralateral cornea compared to the control group. There was no significant difference in corneal nerve and cell parameters between patients with TN with and without involvement of the ophthalmic nerve (V1) or with nerve vessel conflict. Conclusion Corneal confocal microscopy is a rapid non-invasive imaging technique that identifies symmetrical corneal nerve loss in patients with TN.